2013
DOI: 10.1007/s11552-013-9538-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Appropriateness of Patient Transfers for Hand and Microsurgery to a Level I Trauma Center

Abstract: Background The transfer of patients for hand and microsurgical emergencies to level I trauma centers is a common practice. Many of these transfers do not actually require a hand specialist and could be taken care of at most regional hospitals. In this study, we will evaluate the appropriateness of patient transfers for hand trauma and determine if there is a correlation between inappropriate transfers and undesirable factors, such as insurance status and off-hour's presentation. Methods A retrospective chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 12 publications
(18 reference statements)
4
21
0
Order By: Relevance
“…Our rate of inappropriate transfers was 68.5%, which shows that the majority of transfers are adequately stabilized and sent home by the junior resident without the intervention of an attending surgeon. Similar low rates of proper transfers were found in other studies such as Friebe et al (66% inappropriate), 4 Bauer et al (52% never saw a hand surgeon), 2 Gardiner and Hartzell (53% did not require evaluation by a hand surgeon), 5 Ozer et al (65% of patients airlifted for replantation did not get this surgery), 12 and Patterson et al (75% did not need transfer to a level I trauma center). 14 This points to a likely misuse of resources, as an attending physician at the referring hospital could likely stabilize these patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our rate of inappropriate transfers was 68.5%, which shows that the majority of transfers are adequately stabilized and sent home by the junior resident without the intervention of an attending surgeon. Similar low rates of proper transfers were found in other studies such as Friebe et al (66% inappropriate), 4 Bauer et al (52% never saw a hand surgeon), 2 Gardiner and Hartzell (53% did not require evaluation by a hand surgeon), 5 Ozer et al (65% of patients airlifted for replantation did not get this surgery), 12 and Patterson et al (75% did not need transfer to a level I trauma center). 14 This points to a likely misuse of resources, as an attending physician at the referring hospital could likely stabilize these patients.…”
Section: Discussionsupporting
confidence: 78%
“…14 Friebe et al based their assessments on the judgment of a panel of experts. 4 Other reports looked mainly at Injury Severity score. 7,17 However, our investigation did not differ significantly from the methods of Bauer et al, who looked at the highest level of physician who treated patients transferred to their institution.…”
Section: Discussionmentioning
confidence: 99%
“…Uninsured patients have been found to make repeated emergency room visits in search of hand and wrist care referrals [7]. Inappropriate transfers of uninsured or underinsured patients to one level 1 trauma center in Virginia over a 22-month period was found to cost $124,151 in physician charges, facility fees, and transportation [3]. This triage system works well within a healthcare system with an electronic medical record where the referring and receiving physicians can read the same notes and labs and visualize the same pictures and films from hundreds of miles away.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that approximately 70% of hand surgery consults sent to a tertiary center are inappropriate for urgent assessment and could be assessed in clinic. 9,10 Reducing the patient burden in emergency departments also has significant cost-saving benefit. 9 The objective of this study is to examine the volume and type of injuries seen at the University of Alberta plastic surgery resident hand clinic as well as to evaluate patient satisfaction with their treatment at the clinic.…”
Section: Introductionmentioning
confidence: 99%